Lower Cretaceous turtle tracks from Hekou Group of Northwest China. (July 2019) - Xing, Lida; Li, Daqing; Klein, Hendrik; Lockley, Martin G.; Liang, Qingqing; Yang, Jingtao; Li, Longfeng; You, Wenze
Abstract: Two small assemblages of turtle swim tracks from the Hekou Group, Gansu Province, represent the sixth and seventh reports of turtle tracks from the Cretaceous of China. One assemblage from Liujiaxia Dinosaur National Geopark, with seven tracks, is interpreted to represent a partial trackway with a few isolated tracks, and another one with six tracks from the Fangtai site is interpreted to represent turtle swim tracks, including one inferred manus pes set. At least five turtle body fossil taxa are known from the Cretaceous body fossil record in Gansu, and although no one taxon can be matched with the tracks described here based on size all can be considered as possible potential trackmakers.